2017
DOI: 10.1038/s41598-017-02419-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Potentials of Methylene Blue for Human Skin Longevity

Abstract: Oxidative stress is the major cause of skin aging that includes wrinkles, pigmentation, and weakened wound healing ability. Application of antioxidants in skin care is well accepted as an effective approach to delay the skin aging process. Methylene blue (MB), a traditional mitochondrial-targeting antioxidant, showed a potent ROS scavenging efficacy in cultured human skin fibroblasts derived from healthy donors and from patients with progeria, a genetic premature aging disease. In comparison with other widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“…Metformin treatment of HGPS cells results in the down-regulation of progerin expression (Egesipe et al 2016 ; Park and Shin 2017 ). Methylene blue is another anti-oxidant and potential anti-ageing product that seems to have great potential in treating HGPS (Xiong et al 2017 ). Other successful compounds that reduce reactive oxygen species in HGPS include the rho-associated protein kinase (ROCK) inhibitor—Y-27632, reducing DNA damage, improving nuclear shape and restoring mitochondrial function (Kang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin treatment of HGPS cells results in the down-regulation of progerin expression (Egesipe et al 2016 ; Park and Shin 2017 ). Methylene blue is another anti-oxidant and potential anti-ageing product that seems to have great potential in treating HGPS (Xiong et al 2017 ). Other successful compounds that reduce reactive oxygen species in HGPS include the rho-associated protein kinase (ROCK) inhibitor—Y-27632, reducing DNA damage, improving nuclear shape and restoring mitochondrial function (Kang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its low redox potential, MB molecule can switch between its reduced and oxidized forms (MB and MBH 2 respectively), which facilitates mitochondrial electron transport and results in reduced ROS production [6]. Recent studies have shown that MB increases the longevity of skin fibroblasts and improves cell proliferation; thus, it could promote wound healing procedure [7]. Rosique et al studied burn wound healing in an animal model and showed that treatment with MB reduces the progression of burn and accelerates skin recovery [8] but its efficacy in the surgical wound healing process has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that methylene blue is a potent reactive oxygen species (ROS) inhibitor (Poteet et al, 2012 ; Xiong et al, 2017 ), and ROS is important for inducing inflammasome activation in multiple cell types (Zhou et al, 2011 ; Abais et al, 2015 ; Jo et al, 2016 ). To determine whether the effect of methylene blue on inflammasome activation was associated with ROS production, intracellular ROS was analyzed by H2DCFDA staining of microglia.…”
Section: Resultsmentioning
confidence: 99%